2002
DOI: 10.2466/pr0.90.2.654-658
|View full text |Cite
|
Sign up to set email alerts
|

Age, Sex, Education, Religion, and Perception of Tattoos

Abstract: Tattooing has become more acceptable in the mainstream American culture in recent years. Based on a survey with face-to-face interviews of 335 nontattooed adults randomly selected from a city with a population of 444,000, this study explored the relationship of individuals' demographic variables, attitudes toward religion, and their perceptions of tattoos. The hierarchical multiple regression analysis showed that age and attitude toward religion were associated with individuals' perception of tattoos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The relationship of BM and religiosity is unclear. Lin found a weak negative correlation between attitudes toward religion and the perceptions of tattoos [23]. Similarly, Koch et al.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The relationship of BM and religiosity is unclear. Lin found a weak negative correlation between attitudes toward religion and the perceptions of tattoos [23]. Similarly, Koch et al.…”
Section: Discussionmentioning
confidence: 86%
“…The relationship of BM and religiosity is unclear. Lin found a weak negative correlation between attitudes toward religion and the perceptions of tattoos [23]. Similarly, Koch et al reported weak negative correlations between the number of tattoos and the strength of religious faith, as well as between interest in tattoos and church attendance and the strength of religious faith [24].…”
Section: Discussionmentioning
confidence: 98%
“…The gender of the perceiver did not affect attitudes toward tattooed individuals (Baumann et al 2016;Degelman and Price 2002;Dickson et al 2014;Hawkes et al 2004;Zestcott et al 2017). However, age (Deal et al 2010;Dean 2010;Lin 2002;Zestcott et al 2018), being a student, (Dale et al 2009), and a left-wing political orientation (Swami et al 2012;Zestcott et al 2018) have all been associated with a more positive evaluation of tattooed and/or pierced individuals. Thus, if anything, the negative effects found in our relatively young samples with high proportions of students and with left-wing oriented people would have probably been stronger in a representative sample or in more right-wing oriented parts of society.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Whereas research has documented variance in negative attitudes about tattooed individuals in comparison to non-tattooed individuals as a function of the perceiver's occupation (Lin, 2002;Stuppy, Armstrong, & Casals-Ariet, 1998;Swami et al, 2012), few studies have empirically assessed what specific characteristics are associated with tattooed individuals compared to non-tattooed individuals. The research that has been conducted suggests that tattoos operate as a proxy indicator for factors that are commonly associated with the criminal stereotype and that also inform punitiveness in juror decisionmaking, such as lower socio-economic status (Devine et al, 2001;Esqueda, Espinoza, & Culhane, 2008;Hoffman, 1981), masculinity (DeMello, 2000;MacLin & Herrera, 2006), and lower attractiveness (Degelman & Price, 2002;Resenhoeft, Villa, & Wiseman, 2008;Swami & Furnham, 2007).…”
Section: Stereotypes About Tattooed Individualsmentioning
confidence: 99%